2005
DOI: 10.2337/diabetes.54.12.3402
|View full text |Cite
|
Sign up to set email alerts
|

The HMG Box Transcription Factor Sox4 Contributes to the Development of the Endocrine Pancreas

Abstract: To investigate the role of the Sry/hydroxymethylglutaryl box (Sox) transcription factors in the development of the pancreas, we determined the expression pattern of Sox factors in the developing mouse pancreas. By RT-PCR, we detected the presence of multiple Sox family members in both the developing pancreas and mature islets and then focused on two factors, Sox2 and Sox4. The expression field of Sox2, which plays a role in the maintenance of some stem cell populations, included the developing duodenum, but So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 58 publications
4
104
0
Order By: Relevance
“…1B). Of these genes, SOX4/sox4b has been linked to both pancreatic development (16,17) and insulin secretion in the mouse (18), and as such represents a plausible candidate for T2D, whereas cdkal1 in zebrafish is expressed ubiquitously and at low levels (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…1B). Of these genes, SOX4/sox4b has been linked to both pancreatic development (16,17) and insulin secretion in the mouse (18), and as such represents a plausible candidate for T2D, whereas cdkal1 in zebrafish is expressed ubiquitously and at low levels (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…As such, the previous pancreatic studies did not definitively show that cell-autonomous actions of SOX4 in the pancreatic epithelium were necessary [28,31,53]. Furthermore, the early studies did not uncover when SOX4 becomes important for islet cell formation or how it functions to regulate islet cell genesis.…”
Section: Sox4 Regulates Factors Downstream Of Neurog3mentioning
confidence: 78%
“…Null mutation of Sox4 results in cardiac abnormalities, defects in blood flow and embryonic lethality by E14.5 prior to completion of the bulk of endocrine cell differentiation. However, significant reductions of insulin (INS) and/or glucagon (GCG) expression were observed by us and others [29,31].…”
Section: Introductionmentioning
confidence: 99%
“…Our data demonstrate that without normal down-regulation of Neurog3, the β-cell population does not adequately expand and diabetes ensues. Interestingly, however, a very low level of Neurog3 expression persists in adult islets (30)(31)(32)(33). Recent studies demonstrated that this sustained low-level expression of Neurog3 contributes to endocrine function (33).…”
Section: Discussionmentioning
confidence: 99%